Analisis Penggunaan Berkelanjutan Digital Banking Dengan Fitur Layanan Sebagai Variabel Moderasi Pada Nasabah PT. Bank Syariah Indonesia KC Batusangkar - Habil Febrian; Asyari Asyari; Dila Anggraini; Nurul Fadhila Hasanah; Anwar Sholihin (Jurnal Ilmiah Ekonomi Islam, 2023)
This study aims to determine the use of sustainable digital banking with service features as a moderation variable for customers of PT. Bank Syariah Indonesia KC Batusangkar data analysis technique uses PLS (Partial Least Square) with processing using Software Warp-PLS 8.0. The test results using the SEM-PLS approach show that, Moderation effect of service features in the relationship between perceived usefulness and continuance intention in using digital banking during the Covid 19 period. Perceived usefulness of X1 is positive and significant, meaning that service features are able to moderate the relationship between perceived usefulness and use sustainable so that the hypothesis (H4) is accepted. Service features significantly moderate the relationship between perceived usefulness and sustainable use with a p-value